PENGARUH KEKERUHAN AIR TERHADAP EFEKTIFITAS BACILLUS THURINGIENSIS H-14 - Darwin, Akhid (Jurnal Kedokteran YARSI, 2005)
Bacillus thuringiensis H-14 (Bt H-14) usually controled the larvae of Aedes, Culex, and Anopheles. Turbidity could be caused by organic and inorganic substances suspended in water which might disturb the disinfection process. The aim of this study was to know the effectivity of the turbidity and the duration of the exposure in terms of the number of dead of the third instar Anopheles sundaicus larvae. The results showed different effectivity of B. thuringiensis H-14 in terms of the turbidity level and the duration of the exposure after six and twelve hours with the probability value p 0.05.  Doses of  0.5 ? 1.0  L/Ha at the turbidity levels of  30 untill 227 Nephelometric Turbidity Units (NTU) at six hours exposure then the number of dead larvae was less than 50 %,  while the number of dead larvae was more than 50  %  at twelve hours exposure. Effective doses of the B. thuringiensis H-14 after the exposure of twelve hours were 0.5 L/Ha at the level of turbidity of 30 NTU, 0.6 L/Ha at 40 NTU, 0,7 L/Ha at 46 NTU,  and 0.9 L/Ha at 189 NTU respectively, while a dose of  1.0 L/Ha was not effective at 227 NTU  with a number of dead larvae less than 50 %. It was suggested to determine the turbidity of water before the application of B. thuringiensis H-14 in order to obtain the exact and effective dose of the B. thuringiensis H-14 tested